Metode Pemecahan Sistem Kongruensi Linear - Budiman, Muhammad Arief; Kurniadi, Edi; Sukono, Sukono; Sylviani, Sisilia (Department of Mathematics, Faculty of Science and Technology Universitas Jambi, 2024)
A linear congruence system is a system that has more than one linear congruence. The solution of linear congruence systems has an important role in the concept of number theory. Various ways of settlement can be applied in different cases. This study discusses the problem solving of linear congruence systems with the Chinese Remainder Theorem, Intelligent Inspection Algorithm type-I and II and its application.